2006
DOI: 10.1186/1550-2783-3-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements and Sports Performance: Herbals

Abstract: This is the fourth in a series of six articles to discuss the major classes of dietary supplements (vitamins; minerals; amino acids; herbs or botanicals; metabolites, constituents/extracts, or combinations). The major focus is on efficacy of such dietary supplements to enhance exercise or sport performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 35 publications
0
40
0
9
Order By: Relevance
“…Hence, knowledge of the amino acid composition of foods serves as a basis for establishing their potential nutritive value. It may also allow evaluation of changes in nutritive value that may arise in the preparation, processing, and storage of foods [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, knowledge of the amino acid composition of foods serves as a basis for establishing their potential nutritive value. It may also allow evaluation of changes in nutritive value that may arise in the preparation, processing, and storage of foods [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…High doses (supraphysiological doses) of B‐vitamins could ameliorate genetic diseases by stimulating variant enzymes with decreased coenzyme‐binding affinity (increased K m ) (Ames et al, 2002). It is found that athletes who lack B vitamins have reduced high‐intensity exercise performance and are less able to repair damaged muscles or build muscle mass than their peers who eat a diet rich in B‐vitamins (Williams, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Italy ranks as the leading country in Europe for the consumption of plant-based dietary supplements (DS) [3]. These products are not simply used to support sport performances [4], but their non-prescribed use is very frequent also among children and adolescents [5], students [6], pregnant and postmenopausal women [7,8], and oncological patients or those affected by other chronic diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%